2008
DOI: 10.1053/j.gastro.2007.10.030
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Pancreatic Inflammatory Responses and Inhibition of Fibrosis in CD39-Null Mice

Abstract: Background & Aims-Extracellular nucleotides are released from injured cells and bind to purinergic-type 2 receptors (P2-R) that modulate inflammatory responses. Ectonucleotidases, such as CD39/NTPDase1, hydrolyze extracellular nucleotides to integrate purinergic signaling responses. As the role of extracellular nucleotides and CD39 in mediating inflammation and fibrosis are poorly understood, we studied the impact of CD39 gene deletion in a model of pancreatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 27 publications
0
43
1
Order By: Relevance
“…The CD39 family and CD73 participate in an adaptive response to the increase in extracellular nucleotide concentration by increasing their expression and activity to decrease ATP and increase adenosine (7). Increased CD39 expression has been reported in coronary vasculature, lungs, and pancreas during inflammation and tissue damage (8,9,19). Transgenic mice that lack ENTPD1 develop increased pulmonary edema and inflammation compared with control littermates in a ventilator-induced model of lung injury (8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CD39 family and CD73 participate in an adaptive response to the increase in extracellular nucleotide concentration by increasing their expression and activity to decrease ATP and increase adenosine (7). Increased CD39 expression has been reported in coronary vasculature, lungs, and pancreas during inflammation and tissue damage (8,9,19). Transgenic mice that lack ENTPD1 develop increased pulmonary edema and inflammation compared with control littermates in a ventilator-induced model of lung injury (8).…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic mice that lack ENTPD1 develop increased pulmonary edema and inflammation compared with control littermates in a ventilator-induced model of lung injury (8). In the cerulein model of pancreatitis, mice that lack ENTPD1 exhibited less severe atrophy and fibrosis, suggesting that upregulation of ENTPD1 is not protective in this tissue (19). It therefore appears that inhibition of extracellular ATP catabolism can have positive or negative effects, depending on the nature of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Kunzli et al [80] showed P2X 7 R upregulation in pancreatic tissue samples isolated from patients affected by CP with respect to control samples. Moreover, in a study to understand the impact of CD39 gene deletion using a mouse model of the disease, they noted P2X 7 R upregulation [80,81]. Thus, P2X 7 R might be linked with pancreatic remodeling and fibrogenesis.…”
Section: Pancreatic Fibrosismentioning
confidence: 99%
“…Recently, a study using CD39-null mice demonstrated the importance of CD39 and purinergic signaling, potentially acting by P2X7, impacting fibrosis and playing an important role in modulating extracellular matrix remodeling in inflammatory diseases of the pancreas [69].…”
Section: Immunomodulation and Cell-cell Interactionsmentioning
confidence: 99%